2023
DOI: 10.1108/ocj-06-2022-0012
|View full text |Cite
|
Sign up to set email alerts
|

Stress in the cybersecurity profession: a systematic review of related literature and opportunities for future research

Abstract: PurposeThe impact of stress on personal and work-related outcomes has been studied in the information systems (IS) literature across several professions. However, the cybersecurity profession has received little attention despite numerous reports suggesting stress is a leading cause of various adverse professional outcomes. Cybersecurity professionals work in a constantly changing adversarial threat landscape, are focused on enforcement rather than compliance, and are required to adhere to ever-changing indust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 107 publications
0
5
0
Order By: Relevance
“…Working in the field of cyber security has been compared to working in a warlike environment (Brody, 2015;Singh et al, 2023).…”
Section: General Stressors In the Cybersecurity Professionmentioning
confidence: 99%
See 2 more Smart Citations
“…Working in the field of cyber security has been compared to working in a warlike environment (Brody, 2015;Singh et al, 2023).…”
Section: General Stressors In the Cybersecurity Professionmentioning
confidence: 99%
“…Recent studies have indicated that work-related stress is high in the cybersecurity profession (Nobles, 2022;Singh et al, 2023). According to a 2021 CIISec State of Profession report, over half of cybersecurity professionals report having stress-related sleeping issues (Wilson, 2022).…”
Section: General Stressors In the Cybersecurity Professionmentioning
confidence: 99%
See 1 more Smart Citation
“…Working in the field of cybersecurity has been compared to working in a warlike environment (Brody, 2015;Singh, et al, 2023). Cyberspace does not follow geography and threat actors can project their attacks easily to anywhere on the globe making organisations defences endlessly contested.…”
Section: Introductionmentioning
confidence: 99%
“…Cybersecurity professionals are providing critical service to ensure business continuity of organisations and government services in a constantly changing adversarial landscape (Paul & Dykstra, 2017). Recent studies have indicated that work-related stress is high in the cybersecurity profession (Nobles, 2022;Singh, et al, 2023). The VMware Global Incident Response Threat Report from 2022 demonstrates that 51% of cybersecurity professionals self-report having symptoms related to burnout and of that group, 65% have considered leaving the cybersecurity profession altogether (VMware, 2022).…”
Section: Introductionmentioning
confidence: 99%